Negara, pasaran, dan pemodenan Malaysia (Bangi Penerbit Universiti Kebangsaan Malaysia, 2000)
Socioeconomic conditions of modern Malaysia; papers of a workshop.
Includes bibliographical references and index.
Keywords: Community development -- Malaysia -- Congresses; Social problems -- Malaysia -- Congresses; Malaysia -- Economic conditions -- Congresses; Malaysia -- Social conditions -- Congresses